Pengaruh Penggunaan Media Interaktif Pembelajaran Quizizz terhadap Hasil Belajar Geografi Siswa Kelas X SMA N 4 Sumatera Barat - Mardiah, Ainul; Anwar, Syafri (YASIN, 2025)
The low geography learning outcomes among Grade X students, as indicated by scores falling below the standard, serve as the background of this study. One of the main contributing factors is the use of learning methods that lack engagement and interactivity. This research aims to examine the implementation of learning using interactive media, compare learning outcomes between control and experimental classes, and analyze the effect of using interactive media on geography learning outcomes. A quantitative approach with a quasi-experimental design was employed, using purposive sampling to select two classes—E2 as the experimental class and E4 as the control class. Data were collected through observation, documentation, and testing. The research instruments underwent validity and reliability testing, while data analysis included tests of normality, homogeneity, hypothesis testing, and gain analysis. The findings show that the average post-test score of the experimental class using the interactive Quizizz media was 88.63, compared to 74.03 in the control class. This difference indicates a significant positive effect of using Quizizz on students' geography learning outcomes. The study concludes that integrating interactive media such as Quizizz is effective in enhancing learning outcomes, particularly when aligned with students’ characteristics and learning needs. The practical implication recommends that teachers adopt digital interactive media in geography instruction to foster a more engaging and participatory learning environment.